Using video simulations and virtual reality to improve decision-making skills in basketball - Pagé, C.; Bernier, P.-M.; Trempe, M. (Journal of Sports Sciences, 2019)
A large body of literature supports the effectiveness of using video simulations to improve decision-making skills in invasion sports. However, whether these improvements are transferable (from the laboratory to the court/field) and generalizable (from trained to untrained plays) remains unknown. In addition, it remains to be determined whether presenting the video simulations using virtual reality provides an added-value. To investigate these questions, varsity-level basketball players underwent four training sessions during which they observed video clips of basketball plays presented either on a computer screen (CS group) or using a virtual reality headset (VR group). A third group watched footage from NCAA playoff games on a computer screen (CTRL group). Decision-making was assessed on-court before and after the training sessions using two types of plays: "trained" plays (presented during the CS and VR training sessions) and "untrained" plays (presented only during the on-court tests). When facing the trained plays in the posttest, both VR and CS groups significantly outperformed the CTRL group. In contrast, when facing the untrained plays, the VR group outperformed both the CS and CTRL groups. Our results indicate that CS training leads to transferable but non-generalized decision-making gains while VR training leads to transferable and generalized gains.